Posicionamiento de mediadoras escolares de lectura. La Biblocleta como dispositivo didáctico de mediación. - Torres Cárdenas, Ángela Carolina; Chacón Chacón, Adriana; Combariza Salamanca, Luisa Fernanda (Enunciación)
This article is the result of a research that aims to understand how the didactic mediation practices of reading contribute to the strengthening of teacher education processes and therefore, to the positioning of the figure of school mediators in order to favoring the resignification of the school library. The methodology is circumscribed in the Participatory Action Research (IAP) approach, whose dialectical and transforming nature promotes first at all, a collective, collaborative and horizontal work, which led to the creation of a study group called Semillero LEO: El arte de lecturar. Secondly, in the design of a reading mediation proposal supported by a didactic device of neighborhood origin: La Biblocleta, which revealed the need for the exchange of knowledge between community and academic experiences. Among the results are, on a theoretical level, the proposal of a conceptual structure that allowed us to explore the reading biography, learn to value books and understand access to reading as a cultural right, and on a praxis level, the configuration of a learning community that managed to institutionalize Semillero LEO, which will lead a center of interest from the line of reading research for the intermediate and professional cycles of a normal school. In conclusion, it was possible to positioning normal school teachers as reading mediators. In that sense, this research opened new horizons of study to continue mobilizing reading practices that lead, among other things, to reactivate the school library as a space with free access and open doors.